2011
DOI: 10.4269/ajtmh.2011.10-0253
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Malaria in Calabar, Nigeria: The Molecular Perspective

Abstract: Polymerase chain reaction (PCR) has been shown to be more sensitive in detecting low-level parasitemia than conventional blood film microscopy. We estimated the prevalence of congenital malaria using nested PCR amplification of the small subunit 18S RNA gene to detect low-level parasitemia and identify Plasmodium species in 204 mother–neonate pairs. Cord-blood parasitemia was detected in four babies by PCR, giving a prevalence of 2.0%. The newborns of primidgravidae were more susceptible to congenital malaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Only two newborns had mothers with neither peripheral malaria infection nor placental malaria infection. Earlier studies of transplacental malaria reported these associations [11, 18, 24, 30]. A strong association between placental malaria and umbilical cord blood parasitemia has been reported, and this was suggested to be responsible for congenital malaria.…”
Section: Discussionmentioning
confidence: 93%
“…Only two newborns had mothers with neither peripheral malaria infection nor placental malaria infection. Earlier studies of transplacental malaria reported these associations [11, 18, 24, 30]. A strong association between placental malaria and umbilical cord blood parasitemia has been reported, and this was suggested to be responsible for congenital malaria.…”
Section: Discussionmentioning
confidence: 93%
“…Possible explanations could be differences in malaria prevention coverage during pregnancy or laboratory operational factors. Traditional microscopy in routine service laboratories may over-diagnose malaria, and has been shown to have a poor positive predictive value when compared with microscopy from research laboratories [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation between placental and congenital parasitaemia has been reported from previous studies in Calabar. [25] This study has provided a current profile of congenital malaria in Calabar, and would rekindle research focus on maternal and infantile malaria in the study area and other locations. Although the finding in this study compares with the low, 2.0%, prevalence from studies in the University of Calabar Teaching Hospital, reported within the same period; [25] the five-year prevalence profile indicates that congenital malaria was rising from 14.5% in 2011 and 2012 to 21% in 2013, suggesting possible weakness in the mechanism of maternal malaria management in the city.…”
Section: Discussionmentioning
confidence: 99%
“…[23] 5.1% in the University College Hospital, Ibadan, western Nigeria; [24] 2.0% in the University of Calabar Teaching Hospital; [25] 14% in the General Hospital, Minna, North-central Nigeria; [26] and 9.6% in the University of Port Harcourt Teaching Hospital. [27] However, comparatively lower rates have been reported in neighbouring West African countries such as 2.2% in Ghana and 4.7% in Cote d'Ivore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation